Peningkatan Kemampuan melalui Pendidikan Teman Sebaya dalam Upaya Skrining Infeksi Menular Seksual pada Remaja - Dianna, Dianna; Fitriani, Henny; Putri, Riska Regia Catur (Jurnal Pengabdian Bidang Kesehatan, 2024)
Peers have a big influence on changes in individual behavior. Peers can also provide reinforcement, both positive and negative. Peer counseling has the potential to provide positive reinforcement, namely how a friend can become a motivator for other friends. The implementation referred to in this research is the implementation of peer counseling services.This activity will be carried out in 3 stages, namely the initial stage includes surveying community service locations, making proposals and submitting proposals, the second stage is implementing activities where socialization will be carried out about the concept of peers. Then there will be an evaluation of the process of community service activities carried out in a question and answer session for the audience with the presenter or speaker. The final stage is evaluation and reporting of activities. Teenagers are targets in community service activities which are always directed at coordinating with local health workers.The results of the activity show that increasing capacity through peer education in efforts to screen for sexually transmitted infections in adolescents in the Sungai Beliung sub-district in the working area of the Perumnas II Health Center in 2024 has been carried out well.It is hoped that partners can continuously implement media and deliver educational material about STIs by involving teenagers, families and the general public.